Description of Pregnant Women's Perceptions About Physical Changes During Pregnancy at BPM Titin Khamidah SST in Trowulan Village Trowulan District Mojokerto - Heni Purwati; Etik Khusniyati (Kirana Publisher (KNPub), 2024)
Pregnancy is a time of physiological changes, discomfort, and difficulty in adapting, leading many mothers to view it as unnatural. This research aimed to understand pregnant women's perceptions of physical changes during pregnancy. The study involved 39 pregnant women in the first trimester at BPM Titin Khamidah SST, Trowulan Village, Trowulan District, Mojokerto. Data was collected using a questionnaire instrument and processed through editing, coding, scoring, and tabulating. The majority of respondents had positive perceptions (55%), with a small number (45%) having negative perceptions (45%). Factors such as education, age, employment, and information sources influenced these perceptions. A positive perception can reduce anxiety during pregnancy. To improve perceptions, respondents should regularly attend antenatal care (ANC) or read mass media, aiming to change negative perceptions into positive ones.